Functional analysis of the aglycone-binding site of the maize beta-glucosidase Zm-p60.1 - Dopitová, Radka; Mazura, Pavel; Janda, Lubomír; Chaloupková, Radka; Jerábek, Petr; Damborský, Jirí; Filipi, Tomás; Kiran, Nagavalli S; Brzobohatý, Bretislav (The FEBS journal, 2008)
Beta-glucosidases such as Zm-p60.1 (Zea mays) and Bgl4:1 (Brassica napus) have implicated roles in regulating plant development by releasing biologically active cytokinins from O-glucosides. A key determinant of substrate specificity in Zm-p60.1 is the F193-F200-W373-F461 cluster. However, despite sharing the same substrates, amino acids in the active sites of Zm-p60.1 and Bgl4:1 differ dramatically. In members of the Brassicaceae we found a group of beta-glucosidases sharing both high similarity to Bgl4:1 and a consensus motif A-K-K-L corresponding to the F193-F200-W373-F461 cluster. To study the mechanism of substrate specificity further, we generated and analyzed four single (F193A, F200K, W373K and F461L) and one quadruple (F193A-F200K-W373K-F461L) mutants of Zm-p60.1. The F193A mutant showed a specific increase in affinity for a small polar aglycone, and a deep decrease in k(cat) compared with the wild-type. Formation of a cavity with decreased hydrophobicity, and significant consequent alterations in ratios of reactive and non-reactive complexes, revealed by computer modeling, may explain the observed changes in kinetic parameters of the F193 mutant. The large decrease in k(cat) for the W373K mutant was unexpected, but the findings are consistent with the F193-aglycone-W373 interaction playing a dual role in the enzyme's catalytic action; influencing both substrate specificity, and the catalytic rate by fixing the glucosidic bond in a favorable orientation for attack by the catalytic pair. Investigation of the combined effects of all of the mutations in the quadruple mutant of Zm-p60.1 was precluded by extensive alterations in its structure and almost complete abolition of its enzymatic activity.
Keywords: kinetika; rostliny; Models, Molecular; beta-Glucosidase; substrátová specifita; kukuřice setá; rekombinantní proteiny; Recombinant Proteins; Plants; rostlinné proteiny; Protein Conformation; Escherichia coli; molekulární modely; beta-glukosidasa; Zea mays; konformace proteinů; Binding Sites; fylogeneze; Plant Proteins; Brassica napus; Catalytic Domain; Kinetics; Substrate Specificity; katalytická doména; aminokyseliny; Phylogeny; vazebná místa; Amino Acids